Defining the eco-enzymological role of the fungal strain Coniochaeta sp. 2T2.1 in a tripartite lignocellulolytic microbial consortium. Issue 1 (26th November 2019) - Jiménez, Diego Javier; Wang, Yanfang; Chaib de Mares, Maryam; Cortes-Tolalpa, Larisa; Mertens, Jeffrey A; Hector, Ronald E; Lin, Junyan; Johnson, Jenifer; Lipzen, Anna; Barry, Kerrie; Mondo, Stephen J; Grigoriev, Igor V; et al.
ABSTRACT: Coniochaeta species are versatile ascomycetes that have great capacity to deconstruct lignocellulose. Here, we explore the transcriptome of Coniochaeta sp. strain 2T2.1 from wheat straw-driven cultures with the fungus growing alone or as a member of a synthetic microbial consortium with Sphingobacterium multivorum w15 and Citrobacter freundii so4. The differential expression profiles of carbohydrate-active enzymes indicated an onset of (hemi)cellulose degradation by 2T2.1 during the initial 24 hours of incubation. Within the tripartite consortium, 63 transcripts of strain 2T2.1 were differentially expressed at this time point. The presence of the two bacteria significantly upregulated the expression of one galactose oxidase, one GH79-like enzyme, one multidrug transporter, one laccase-like protein (AA1 family) and two bilirubin oxidases, suggesting that inter-kingdom interactions (e.g. amensalism) take place within this microbial consortium. Overexpression of multicopper oxidases indicated that strain 2T2.1 may be involved in lignin depolymerization (a trait of enzymatic synergism), while S. multivorum and C. freundii have the metabolic potential to deconstruct arabinoxylan. Under the conditions applied, 2T2.1 appears to be a better degrader of wheat straw when the two bacteria are absent. This conclusion is supported by the observed suppression of its (hemi)cellulolytic arsenal and lower degradation percentages within the microbial consortium. Abstract : This study reports the differential expression profiles of the fungal strain Coniochaeta sp. 2T2.1 growing in a tripartite wheat straw-degrading microbial consortium.